Mental health predictive factors in infertile couples - Z Khosravi (JRI, 2002)
Infertility affects different aspects of the individual’s life and perhaps it is one of the main life stressors. Individuals under major stress are more exposed to disease such as depression, anxiety, low self confidence and dissatisfaction. The present study focuses on the role of gender on mental health in infertile couples. The sample was 50 infertile couples. The results indicated, infertile women have more psychological problems than infertile men, perceive infertility as more negative than men and hope to the future and to marital life, and the sense of meaning in life have determining roles in predicting mental health of infertile couples.
Keywords: Infertility, Mental health, Gender, Infertile couples